Long‐term monitoring of wildlife populations for protected area management in Southeast Asia. Issue 2 (21st December 2021) - Nuttall, Matthew N.; Griffin, Olly; Fewster, Rachel M.; McGowan, Philip J. K.; Abernethy, Katharine; O'Kelly, Hannah; Nut, Menghor; Sot, Vandoeun; Bunnefeld, Nils
Abstract: Long‐term monitoring of biodiversity in protected areas (PAs) is critical to assess threats, link conservation action to species outcomes, and facilitate improved management. Yet, rigorous longitudinal monitoring within PAs is rare. In Southeast Asia (SEA), there is a paucity of long‐term wildlife monitoring within PAs, and many threatened species lack population estimates from anywhere in their range, making global assessments difficult. Here, we present new abundance estimates and population trends for 11 species between 2010 and 2020, and spatial distributions for 7 species, based on long‐term line transect distance sampling surveys in Keo Seima Wildlife Sanctuary in Cambodia. These represent the first robust population estimates for four threatened species from anywhere in their range and are among the first long‐term wildlife population trend analyses from the entire SEA region. Our study revealed that arboreal primates and green peafowl ( Pavo muticus ) generally had either stable or increasing population trends, whereas ungulates and semiarboreal primates generally had declining trends. These results suggest that ground‐based threats, such as snares and domestic dogs, are having serious negative effects on terrestrial species. These findings have important conservation implications for PAs across SEA that face similar threats yet lack reliable monitoring data. Abstract : We present abundance estimates and population trends for 11 species between 2010 and 2020 and spatial distributions for 7 species from Cambodia. Our study revealed that arboreal primates generally had either stable or increasing population trends, whereas ungulates and semiarboreal primates generally had declining trends. This suggests that ground‐based threats, such as snares and domestic dogs, are having serious negative effects on terrestrial species.